Prevalence and associated factors of sleeping pills use among students in a Malaysian university - Al-Naggar, Redhwan Ahmed; Md Isa, Zaleha; Musa, Ramli (ASEAN Federation of Psychiatry, 2010)
Objective: This paper aimed to determine the prevalence of sleeping pills use among university students and its associated factors in Malaysia. Methods: This cross-sectional study was conducted in January 2010 among 200 students from Management and Science University (MSU), Shah Alam, Malaysia. The survey was conducted by distributing self-administered questionnaires. The questionnaire was developed based on the literature review. The students were chosen randomly using convenience sampling. Results: A total of 200 university students participated in this study. The prevalence of using sleeping pills among university students is 7.5%. The majority of the participants were Malay 146 (73.0%), from urban area 169 (84.5%), from medical and health sciences background 101 (50.5%). This study showed that there is a significant relationship between using sleeping pills and depression (p= 0.03). There is also a significant relationship between using sleeping pills and inducing sleep by reading (p=0.04). Conclusion: The prevalence of sleeping pills usage among university students is relatively high. This study showed that there is a significant relationship between using sleeping pills and depression.